An Analysis Of The Accounting For Employee Income Supplement (TPP) Budget Responsibility At Disdikbud - Sanjaya, Dendi; Susanti, Neri; Abi, Yudi Irawan (Jurnal Fokus Manajemen, 2024)
The accountability report must be able to trace the inefficiencies of each component, so that corrective actions can be taken if a situation is found that may cause the established goals to not be achieved. The purpose of this research is to analyze the accounting for the responsibility of the Additional Income Budget of Employees (TPP) at DISDIKBUD Seluma Regency. Data collection was conducted through interviews, and the analysis method used in this study is descriptive method. The results of the study show that the organizational structure at the Department of Education and Culture of Seluma regency for the implementation of the TPP budget is considered good due to the separation of responsibilities. The TPP budgeting is carried out by the budget planning department, while the disbursement of TPP is executed by the finance department. The budget preparation at the department is based on the Decree of the Regent of Seluma Regency, and the budget disbursement is done by proposing the TPP amount from each employee to the treasurer. The treasurer then compiles a summary for all employees' TPP, which is then reviewed by the PPK before being submitted to the Head of Department for approval. Once approved, the TPP can be disbursed. The Department of Education and Culture of Seluma regency has not adequately separated controllable and uncontrollable costs, as the TPP expenses are included in controllable costs. The department has prepared accountability reports in the form of TPP budget realization reports. In the accountability report, it can be seen the comparison between the budget and its realization, as well as the differences. For the year 2022, the budget realization was 93.62%, and for 2023, it was 89.83%. This budget surplus occurred due to deductions in TPP for employees who committed violations such as arriving late, not clocking in, and performance not meeting working hours